Investigating the Apoptosis Ability of Ethylenediamine 8-Hydroxyquinolinato Palladium (II) Complex - Hassan Mansouri-Torshizi; Elham Rezaei; Farzaneh Kamranfar; Mostafa Heidari Majd (Tabriz University of Medical Sciences, 2016)
Purpose: High solubility, low renal toxicity and apoptosis-inducing ability of palladium complexes are the reasons for their synthesis. Methods: In vitro cytotoxic study of previously synthesized [Pd(en)(8HQ)]NO3 , was carried out on breast cancer MCF-7 cell lines and prostate cancer DU145 cell lines. DNA fragmentation indicative of apoptotic was also evaluated by TUNEL assay on DU145 cell line. Results: FT-IR spectra of final complex confirmed the existence of chelating ligands. The DU145 cells unlike the MCF-7 cells, demonstrated the significant influence of the Pd (II) complex. The IC50 values of [Pd(en)(8HQ)]NO3 and cisplatin on DU145 cells were 27 and 8.3 μM, respectively. Moreover, nearly 38% apoptosis was evident in DU145 cells after treatment with [Pd(en)(8HQ)]NO3. Conclusion: [Pd(en)(8HQ)]NO3 has great potential in DNA binding and induction of apoptosis; thus it can be used in the future against prostate cancer.